The Effect of Variation in the Length of Water Hyacinth Fiber Twisted on Split Tensile Strength High-Performance Fiber Concrete - Verdian, Riki; Muin, Resmi Bestari (ASTONJADRO, 2023)
One of the weaknesses of concrete is that it has a very small tensile strength, which makes it brittle. Normal concrete has a tensile strength of 9-15% of its compressive strength. To increase the tensile strength of concrete, it is necessary to add fiber. The types of fibers that can be used in concrete can be either natural fibers or non-natural fibers. Various alternatives can be made as an effort to improve the quality of concrete. One of them is by utilizing weeds or weeds into useful materials. One of these disturbing plants is the water hyacinth plant, which is quite abundant and grows very fast. Water hyacinth plants consist of stems, leaf petals, which are rich in fiber, which allows it to be used as an alternative additive in concrete mixtures for construction. The purpose of this research is to try to apply water hyacinth fiber (SEG) 0,75% in high performance concrete (HPC) to determine the effect of the ratio of water hyacinth fiber twisted length on the compressive strength and split tensile strength of high performance concrete with several variants fiber lengths of 2 cm, 1,5 cm and 1 cm. The results showed that the decrease in the compressive strength of water hyacinth fiber-rolled concrete for variations of 2 cm, 1,5 cm and 1 cm were respectively 10,76%, 14,16%, and 18,76% of the reference concrete compressive strength of 45,42 MPa and the highest splitting tensile strength of concrete is in the 1 cm fiber length variation of 3,65 MPa which is 9.89% of the concrete compressive strength of 36,90 MPa. The modulus value decreases with the variation in the length of the fiber strand.